Pemanfaatan Market Digital Dalam Meningkatkan Minat Kewirausahaan Terhadap Siswa dan Siswi MA Annur Pagar Jati Bengkulu Tengah - Aliano, Dio; Zoniarti, Zoniarti; Wagini, Wagini; Gayatri, Ida Ayu Made Er Meytha (Jurnal Dehasen Mengabdi, 2024)
In the era of globalization and the rapid development of information technology, digitalization has entered into various aspects of life, including in the fields of education and entrepreneurship. The utilization of the digital market is one of the important innovations in the business world that provides various opportunities and conveniences for entrepreneurs including for students. This service aims to explore the utilization of the digital market in increasing entrepreneurial interest among MA Annur Pagar Jati students in Central Bengkulu. This research uses the Participatory Action Research (PAR) method with a special study approach involving observation, in-depth interviews. The results showed that digital markets, such as e-commerce and social media have great potential to increase students' entrepreneurial interest and skills. Through various digital-based trainings and projects, students not only learn about entrepreneurial concepts but also gain practical experience in running a business online. In addition, the use of digital marketplaces also helps students develop other skills such as time management, communication and creativity. This indicates that the integration of digital marketplaces in the entrepreneurship curriculum can be an effective strategy to motivate and equip young people with relevant skills to face future economic challenges.